Spray Drying Modelling using Advanced Vaporization Approach - Bello, A.; Ademola, B. R.; Isah, U. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study develops a deterministic mathematical model for simulating the spray drying of pineapple juice. The model applies advanced vaporization kinetics and a receding interface-porous diffusion approach to predict moisture content, droplet density, and temperature. Validated experimentally at feed solids concentrations of 20% and 40% and drying temperatures of 130 °C and 140 °C, the model accurately predicted final moisture content with absolute errors ranging from 2.3% to 5.2% as drying gas temperature decreases from 140 °C to 130 °C for the 20% feed, and from 1% to 1.8% for the 40% feed. Key results quantitatively demonstrate that higher air temperatures reduce final moisture content and reveal the critical role of crust formation in shifting the drying kinetics from a rapid evaporation phase to a slower, diffusion-limited regime. The model's computational efficiency and physics-based foundation make it a valuable tool for the optimization of spray drying processes, potentially reducing reliance on costly and time-consuming experimental trials.